2013
DOI: 10.1016/j.mce.2013.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of estrogen receptor beta isoforms in prostate cancer through interplay between transcriptional and translational regulation

Abstract: Estrogen receptor β (ERβ) and its isoforms have different putative functions and expression patterns in prostate cancer. Current studies on 5′-most exons, 0K and 0N, show that their respective promoters are actively involved in transcription. These data, however, do not explain why ERβ isoforms are differentially expressed in normal and cancerous tissues, since 0K and 0N transcripts are detectable in clinical specimens. Various combinations of 5′ untranslated exons, termed exon 0Xs, associate with promoter 0K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…The human ERβ gene possesses three promoters. The presence of untranslated internal exons and 5 -untranslated region (5 -UTR) variants inserted near the exons is controversial: Moore et al [19] and Lee et al [10] reported the alternative inclusion of multiple untranslated internal exons (0X1-0X8) between exons 0K and 1, whereas Hirata et al [14] and Smith et al [11,12] did not report their presence. The rat ERβ gene was reported to contain three promoters (E1/P2, 0N/P1, and 0H) [13,15], but no untranslated internal exons have been documented.…”
Section: Genomic Organization Of Human and Rat Erβ Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…The human ERβ gene possesses three promoters. The presence of untranslated internal exons and 5 -untranslated region (5 -UTR) variants inserted near the exons is controversial: Moore et al [19] and Lee et al [10] reported the alternative inclusion of multiple untranslated internal exons (0X1-0X8) between exons 0K and 1, whereas Hirata et al [14] and Smith et al [11,12] did not report their presence. The rat ERβ gene was reported to contain three promoters (E1/P2, 0N/P1, and 0H) [13,15], but no untranslated internal exons have been documented.…”
Section: Genomic Organization Of Human and Rat Erβ Genesmentioning
confidence: 99%
“…Transcription of ERβ genes is initiated by activation of multiple promoters. Human and rat ERβ genes were reported to possess three promoters (E1, 0N, and 0K in humans, and E1/P2, 0N/P1, and 0H in rats) [10][11][12][13][14][15]. However, few studies have reported on species differences in patterns of alternative ERβ gene promoter usage.…”
Section: Introductionmentioning
confidence: 99%
“…One other confounding factor occurring in prostate cancer is the expression of the ERb splice variant ERb2. As rodents do not express this splice variant, conclusions about its role in prostate cancer have come from its measurement in prostate cancers (Fujimura et al 2001, Lee et al 2013 and from overexpression in cell lines (Dey et al 2012). So far, there is agreement that the expression of ERb2 in prostate cancer is associated with a poor prognosis (Leung et al 2010).…”
Section: Studies On Erbmentioning
confidence: 99%
“…Distinct cis ‐regulatory sequences in the human ERβ gene confer a molecular architecture that facilitates alternative splicing in prostate and mammary glands, raising the possibility that these same molecular mechanisms contribute to brain‐region specific splicing. For example, full‐length hERβ transcription can be initiated from two different promoters characterised as 5′ untranslated exons, 0K and 0N, in the prostate and mammary glands . In the prostate gland, hERβ1 and hERβ2 were predominantly transcribed from the 0N promoter, whereas hERβ5 was uniquely transcribed from the 0K promoter .…”
Section: Regulation Of Erβ Alternative Splicingmentioning
confidence: 99%
“…[57][58][59] In the prostate gland, hERβ1 and hERβ2 were predominantly transcribed from the 0N promoter, whereas hERβ5 was uniquely transcribed from the 0K promoter. 58 By contrast, both hERβ1 and hERβ5 were transcribed from the 0K promoter in benign and malignant mammary epithelial cells. 60 Depending on the site of transcription initiation, the nascent RNA transcript will include different lengths of 5′ untranslated sequences (UTRa and UTRc), which can have stable secondary structures preventing translation of the RNA product.…”
Section: Cis-and Trans-regulatory Elementsmentioning
confidence: 99%